The Effectiveness of Cooperative Methods and Interactive Digital Media on Elementary School Learning Interest - Didit Darmawan; Mas Ummu Chasbiyah; Anggraini Novita Sari (Molang: Journal Islamic Education, 2026)
In the digital age, the learning process must innovate to maintain students' optimal learning interest. Students tend to be more engaged in learning that involves interactive digital media than in conventional teacher-centered methods. This study aims to analyze the effectiveness of cooperative learning and the use of interactive digital media in enhancing the learning interest of elementary school students. The method used is qualitative with a literature review approach through the analysis of relevant scientific sources from journals, books, and academic publications. Data were analyzed using content analysis by examining and comparing the results of previous studies. The findings indicate that cooperative learning is effective in increasing student participation, collaboration, and learning engagement. Furthermore, interactive digital media such as animations, quizzes, and educational videos have been proven to make learning more engaging and reduce student boredom. The combination of these two approaches consistently enhances students' learning interest at the elementary school level. Thus, it can be concluded that the integration of cooperative learning and interactive digital media is effective in creating active, interactive learning experiences that align with the characteristics of students in the digital age.